Dinamika Hukum Perdagangan Internasional: Tantangan dan Peluang di Era Proteksionisme - Ikhsan, Mohammad; Sefriani, Sefriani (IAI Nasional Laa Roiba Bogor, 2025)
This research explores the significant shifts in the landscape of international trade law prompted by the resurgence of protectionism and neo-mercantilism in the modern era. Following decades of economic liberalization—marked by the establishment of the WTO and reduction of tariff barriers—recent trends indicate growing state intervention through protective policies, tariffs, and non-tariff measures. These developments have intensified geopolitical tensions, undermined the effectiveness of the WTO, and led to the fragmentation of the global legal order. The formulation of the problem in this research are: (i) how does protectionism affect the stability of the international trade legal system? and (ii) what are the challenges and opportunities faced by Indonesia in the era of protectionism? Using a normative-legal approach, this study analyzes the impact of protectionism on the stability of international trade law while identifying opportunities for reform toward a more inclusive and adaptive legal framework. The article also maps Indonesia’s position amid this global dynamic, examining domestic policy responses such as the QRIS and GPN systems, and strategic opportunities in digital economy and regional agreements like RCEP. Findings reveal that protectionism is not merely an economic challenge, but a threat to the integrity of the rules-based trade system. A comprehensive legal response is needed, including institutional reform of the WTO, and harmonization of cross-border digital law. For Indonesia, these challenges also present an opportunity to strengthen a resilient, equitable, and sovereign legal system amidst global trade complexity.